Inclusive Organizational Behavior and Organization Innovation in Pakistan: A Role of Innovative Employee Behavior - Ghulam Muhammad; Taha Gul Khan; Sana Aziz; Rizwana Rasheed; Muhammad Asif Khan; Shumaila Naz (Journal of Management Practices, Humanities and Social Sciences, 2023)
The current study focuses on the mediating role of Innovative Employee Behavior (IEB) between Inclusive Organizational Behavior (IOB) and Organization Innovation (OI). The data were gathered through a structured 5 points Likert scale questionnaire from 298 respondents working in the textile industry of Pakistan. The data were analyzed by using Smart PLS v 3.2.8. Results confirmed the mediating role of Innovative Employee Behavior (IEB) between Inclusive Organizational Behavior (IOB) and Organization Innovation (OI). Results also found that the IOB has a significant positive relationship with IEB and OI. Limited studies have been done on the mediating role of IEB by using the Diffusion of Innovation (DOI) theory in developing countries.